2007
DOI: 10.1063/1.2423139
|View full text |Cite
|
Sign up to set email alerts
|

Optical anisotropy in [hkil]-oriented wurtzite semiconductor quantum wells

Abstract: An 8 ϫ 8 band edge potential matrix of the ͓hkil͔-oriented wurtzite Hamiltonian is developed and applied to explore optical anisotropy in ͓hkil͔-oriented wurtzite semiconductor quantum wells. The wave-vector-dependent optical matrix elements are expressed entirely in terms of Hamiltonian matrix elements, thus avoiding the requirement to introduce any additional optical parameters. To accommodate the noncubic symmetry of the wurtzite lattice, spinor rotation is taken into account when performing the calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Moreover, a strong electrostatic field is induced at the heterointerface of AlGaN / GaN as grown on sapphire, due to the spontaneous and piezoelectric polarizations along the polar c axis. [20][21][22] Therefore, in M-plane GaN, the detailed information of dislocation is necessary for the understanding of its role in optical and electronic properties. In order to avoid the internal electrostatic field, Waltereit et al demonstrated that AlGaN / GaN grown along the ͓1100͔ direction on a ␥-LiAlO 2 substrate significantly enhanced luminous quantum efficiency.…”
mentioning
confidence: 99%
“…Moreover, a strong electrostatic field is induced at the heterointerface of AlGaN / GaN as grown on sapphire, due to the spontaneous and piezoelectric polarizations along the polar c axis. [20][21][22] Therefore, in M-plane GaN, the detailed information of dislocation is necessary for the understanding of its role in optical and electronic properties. In order to avoid the internal electrostatic field, Waltereit et al demonstrated that AlGaN / GaN grown along the ͓1100͔ direction on a ␥-LiAlO 2 substrate significantly enhanced luminous quantum efficiency.…”
mentioning
confidence: 99%
“…8) In semiconductor physics, the conventional kÁp formalism does not take into account the tetrahedral symmetry within a unit cell. [9][10][11][12][13][14][15][16][17] However, this symmetry property can be accounted for by inserting the Kane B 0 parameter terms (i.e., B 0 k x k y , B 0 k y k z , and B 0 k x k z ) into the conventional sp 3 kÁp Hamiltonian matrix. 8,9,17) Accordingly, the aim of this study is to incorporate bulk (or intracell) inversion asymmetry into the matrix elements of the conventional 8 Â 8 kÁp Hamiltonian and optical matrix.…”
Section: Introductionmentioning
confidence: 99%
“…In the following the primes are omitted. It is also noteworthy that calculations for wurtzite show that all the material parameter tensors as well as the misfit strain contributions do not depend on the angle φ (Bykhovski et al, 1993;Chen et al, 2007;Landau & Lifshitz, 1986).…”
Section: Crystal Orientationmentioning
confidence: 99%